DNA Barcoding for Identification of Helopeltis sp. from Kaliwining Experimental Station using Mitochondrial COI Gene - Pancaningtyas, Sulistyani; Tunjung Sari, Ariza Budi; Rahayu, Dwi Suci (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
Helopeltis sp. is one of the major pests of the cocoa plant. Helopeltis can decrease cocoa yield by 50 to 60%. Several species of Helopeltis spp. are still often misidentified due to similarity in morphology such as size and color. This study aimed to identify Helopeltis sp. through DNA barcoding using the mitochondrial cyto- chrome C oxidase subunit 1 (COI) gene. Analysis was carried out on 100 adults Helopeltis sp. from Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute (ICCRI), Jember, Indonesia. Specimens were preserved in 96% ethyl alcohol at 4oC until molecular studies were carried out. PCR amplification was conducted through specific primer from COI gene. Sequences data analysis using MEGA 5.05 software was carried out. The study results using DNA barcoding showed that Helopeltis samples in Kaliwining cocoa plantations are Helopeltis bradyi with a percentage identity above 99% and E value of 0; this sequence as significantly matched. Mean length of the sequences was 679.5 base pairs. Phy- logenetic tree data also shows that the Helopeltis species analysed were also of the same descent, H. bradyi with the accession number KT189562.1. Helopeltis sp. specimens were clustered together. No taxonomic deviation was detected at the species level, indicating that most of the examined species of Helopeltis sp. could be authenticated by the barcode approach using the COI gene. In addi- tion, Helopeltis specimens were also aligned with H. antonii and H. theivora from the genebank to determine their genetic relationship.